Playing Puzzles Improves School-Age Children's Handwashing Knowledge and Skills - Yuliana, Yuliana; Chifdillah, Nino Adib; Rahayu, Eka Putri; Hendriani, Dwi (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Handwashing refers to the practice of using soap and water to clean one's hands, both externally and between the fingers. Avoiding the spread of diarrhea, an infectious disease, requires regular handwashing. The goal of this research is to examine how SDN 009 Loa Janan Ilir students' handwashing knowledge and skills changed after receiving health education in the form of puzzles. Methods: A non-random control group design was used in this quasi-experimental study. The treatment group was SDN 009 Loa Janan Ilir, and the comparison group was SDN 007 Loa Janan Ilir. Each school used a sample size of 53 students. Media with a puzzle theme was provided to the treatment group, while media with a PowerPoint theme was provided to the comparison group. The data was analyzed using Wilcoxon and Mann-Whitney tests.   Results: A bivariate analysis demonstrated that both participants' knowledge and skills improved after being exposed to health education content presented in puzzle form. After receiving health education, there was a statistically significant difference in both the knowledge and competence levels of handwashing between the treatment and comparison groups (ρ-values of knowledge ρ=0.032 and ρ-values of skill ρ=0.000). Conclusion: Students at SDN 009 Loa Janan Ilir learned new information and improved their handwashing skills after obtaining health education via puzzle media, according to the results of this study.